ЯКІСНІ ТА КІЛЬКІСНІ ЗМІНИ В СКЛАДІ СТУДЕНТСТВА НАДДНІПРЯНСЬКОЇ УКРАЇНИ (КІНЕЦЬ ХІХ СТ. – 1914 Р.) (Zaporizhzhia Historical Review, 2021)
In the article the author examines the change in composition of the student society of the Ukrainian institutes of higher education, which were on the territories of the Russian empire at the end of ХІХth century – in 1914. The process of creation of higher educational establishments in Naddnipryans’ka Ukraine, the dynamics of quantitative and class changes of composition of their contingent are probed. The process of democratization of social structure of student society which conduces to its politicization is analyzed.